Targeting ion homeostasis in metabolic diseases: Molecular mechanisms and targeted therapies - Yanjiao Zhang; Kaile Ma; Xinyi Fang; Yuxin Zhang; Runyu Miao; Huifang Guan; Jiaxing Tian (Pharmacological Research)
The incidence of metabolic diseases—hypertension, diabetes, obesity, metabolic dysfunction-associated steatotic liver disease (MASLD), and atherosclerosis—is increasing annually, imposing a significant burden on both human health and the social economy. The occurrence and development of these diseases are closely related to the disruption of ion homeostasis, which is crucial for maintaining cellular functions and metabolic equilibrium. However, the specific mechanism of ion homeostasis in metabolic diseases is still unclear. This article reviews the role of ion homeostasis in the pathogenesis of metabolic diseases and assesses its potential as a therapeutic target. Furthermore, the article explores pharmacological strategies that target ion channels and transporters, including existing drugs and emerging drugs under development. Lastly, the article discusses the development direction of future therapeutic strategies, including the possibility of gene therapy targeting specific ion channels and personalized therapy using novel biomarkers. In summary, targeting ion homeostasis provides a new perspective and potential therapeutic approach for the treatment of metabolic diseases.